La técnica de enseñanza en el modelo ludotécnico: su aplicación a la educación física en primaria - Valero Valenzuela, Alfonso (KRONOS, 2007)
This article tries to set a theoretical starting point for a new Recreational-technical Teaching Style, focusing in teaching-learning process and students chacarcteristics. It is a Model based on traditional straight order in stuff related to topics selection, classroom control, task presentation and feeling like patterns. Meanwhile, it tends to be more inductive in aspects related with teahing interactions, learning rhythm and tasks improvement. Teacher is responsible in some part, however, student has to solve prolemns, think about questions, evaluate and offer suggestions, too. That is why it is an inclusive Model, suitable for Physiscal Education field, where most of the students are involved, no matter their heterogeneity, helping with their global education as persons. At the end, a session is included as an example to see theoretical foundation applied.